2022
DOI: 10.1002/anie.202206866
|View full text |Cite
|
Sign up to set email alerts
|

Property‐Driven Development of Passively Permeable Macrocyclic Scaffolds Using Heterocycles**

Abstract: Passive membrane permeability is a fundamental challenge in the development of bioactive macrocycles. To achieve this objective, chemists have resorted to various strategies, the most common of which is deployment of N‐methylated amino acids and/or D‐amino acids. Here we investigate the effect of heterocyclic grafts on the passive membrane permeability of macrocycles and report the structural consequences of iterative amino acid replacement by azole rings. Through stepwise substitution of amino acid residues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…While the current generation of macrocycles are not active within cells, enhancing the permeability of such compounds is a topic of intense current interest. Accordingly, we anticipate that application of emerging strategies, including promising new experimental [50,51] and computational methods, [52] to these series of macrocyclic OGT inhibitors will be a productive future line of research that will ultimately deliver selective cell-active allosteric OGT inhibitors. Finally, the ability to append a biotin affinity tag to these OGT-targeted macro-cycles, without perturbing the high affinity of these compounds, enables the efficient isolation of OGT samples through a simple one-step affinity purification.…”
Section: Discussionmentioning
confidence: 99%
“…While the current generation of macrocycles are not active within cells, enhancing the permeability of such compounds is a topic of intense current interest. Accordingly, we anticipate that application of emerging strategies, including promising new experimental [50,51] and computational methods, [52] to these series of macrocyclic OGT inhibitors will be a productive future line of research that will ultimately deliver selective cell-active allosteric OGT inhibitors. Finally, the ability to append a biotin affinity tag to these OGT-targeted macro-cycles, without perturbing the high affinity of these compounds, enables the efficient isolation of OGT samples through a simple one-step affinity purification.…”
Section: Discussionmentioning
confidence: 99%
“…Together with George Saunders, we have implemented a property-driven path towards privileged macrocyclic scaffolds that should facilitate rational design strategies in macrocycle-driven drug discovery. 29 Because unusual conformations can be stabilized in constrained environments, we now wonder if conformation/activity studies can be performed on large rings akin to how structure/activity relationships are being done in drug discovery programs. This exciting possibility suggests new avenues for the discovery of bioactive molecules.…”
Section: Synlett Account / Synpactsmentioning
confidence: 99%
“…[14] We also demonstrated that 1,3,4-oxadiazole-based systems can stabilize intramolecular hydrogen-bond networks and help to impose conformationally rigid turn motifs in cyclic peptides (Figure 1A). [15][16][17] In addition to their utility in pre-organizing conformations, heterocyclic motifs possess reactivity that can be exploited in peptide macrocycles. For example, the aziridine functionality embedded within peptide backbones can lead to effective and site-specific late-stage ring expansion (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that 1,3,4‐oxadiazole‐based systems can stabilize intramolecular hydrogen‐bond networks and help to impose conformationally rigid turn motifs in cyclic peptides (Figure 1A). [15–17] …”
Section: Introductionmentioning
confidence: 99%